CGIAR Women Scientists invited to showcase livestock emissions mitigation potential at the USAID-supported Climate and Clean Air Conference - Flintan, Fiona E.; Spinelli, Madison (CGIAR System Organization, 2024)
A news post recapping the CGIAR Research Initiative on Livestock and Climate's engagement at the 2024 Climate and Clean Air Conference in Nairobi, Kenya.